Analisis Perbandingan Nilai Suaian Mounting Main Pin pada Bucket Hitachi EX3600 BU0052 - Sadat N S Sidabutar; Budha Maryanti; Rahmat Tri Wahyudi (University of Merdeka Malang, 2021)
ABSTRACTMounting the main pin on the HITACHI EX3600 bucket is one of the components of the bucket that supports unit work in mining production at PT. THIESS, material wear is one of the problems encountered considering the mounting main pin is used as a place to place the bushing which minimizes friction between the mounting main pin and the bucket pin. Giving an adjusted value to the mounting hole of the main pin is one of the more concerns in order to reduce maintenance costs and repair costs in order to increase the company's profit value. This research was conducted at PT. THIESS, Balikpapan Support Facilities which will be implemented in a period of approximately 3 months. This study uses data collection techniques including: literature study, observation, interviews, and documentation. The independent variables in this study are the number of samples as much as 1 main pin mounting hole (9 measurement points), the dependent variable is the comparison of the effect of the adjustment value on the efficiency of repair costs, and the control variable is measuring the percentage of wear and tear with an adjustment limit of -0.15mm. from the outer diameter of the bushing of 200.34 mm – 200.39 mm. Based on the measurement data and calculation results on the efficiency of repair costs, it shows results of 0.08% and can save repair budget costs up to 2,157.20. Thus, the comparison of the adjustment value that is still within the size tolerance limit will be able to save repair costs of 2,157.20 compared to the custom value that has passed the size tolerance limit above 200.20 mm. The highest percentage of wear occurs at points A1I.b worth 47% and the lowest percentage of wear occurs at points A1I.a, A1III.a, A1III.b, A1III.c with a value of 27%. Meanwhile, the highest wear rate occurs at points A1I.a and A1I.b with a wear rate value of 0.0000448934 mm/hour and the smallest wear rate occurs at points A1III.a A1III.b with a wear rate value of 0.000016835 mm/hour. Keywords : mounting main pin, wear rate, efficiency. ABSTRAKMounting main pin pada bucket HITACHI EX3600 merupakan salah satu komponen bucket yang mendukung kerja unit dalam produksi pertambangan di PT. THIESS, keausan material menjadi salah satu problem yang ditemui mengingat mounting main pin digunakan sebagai tempat peletakan bushing yang meminimalisir gesekan antara mounting main pin dengan pin bucket. Pemberian nilai suaian pada lubang mounting main pin menjadi salah satu perhatian lebih agar dapat menekan biaya perawatan maupun biaya perbaikan guna meningkatkan nilai profit perusahaan. Penelitian ini dilakukan di PT. THIESS, Balikpapan Support Facilities yang dilaksanakan dalam kurun waktu kurang lebih selama 3 bulan. Penelitian ini menggunakan teknik pengumpulan data diantaranya: studi literatur, observasi, interview, dan dokumentasi. Adapun variabel bebas pada penelitian ini adalah jumlah sampel sebanyak 1 lubang mounting main pin (9 titik pengukuran), variabel terikat perbandingan pengaruh besar nilai suaian terhadap efisiensi repair cost, dan variabel kontrol pengukuran persentase keausan dan laju keausan dengan limit suaian sebesar -0,15mm dari diameter luar bushing sebesar 200,34 mm – 200,39 mm. Berdasarkan data pengukuran dan hasil perhitungan pada efisiensi biaya perbaikan menunjukkan hasil sebesar 0,08% dan dapat menghemat biaya anggaran perbaikan hingga 2,157.20. Dengan demikian, perbandingan nilai suaian yang masih berada dalam limit toleransi ukuran akan dapat menghemat biaya perbaikan sebesar 2,157.20 dibandingkan dengan nilai suaian yang telah melewati limit toleransi ukuran diatas 200,20 mm. Persentase keausan tertinggi terjadi pada titik A1I.b senilai 47% dan persentase keausan terendah terjadi pada titik A1I.a, A1III.a, A1III.b, A1III.c dengan nilai 27%. Sedangkan untuk laju keausan tertinggi terjadi pada titik A1I.a dan A1I.b dengan nilai laju keausan sebesar 0,0000448934 mm/jam dan laju keausan terkecil terjadi pada titik A1III.a A1III.b dengan nilai laju keausan sebesar 0,000016835 mm/jam Kata kunci : mounting main pin, laju keausan, efisiensi.